PENGEMBANGAN BUKU TEKS BERBASIS PjBL UNTUK MENUMBUHKAN KARAKTER BERWAWASAN LUAS ANAK - Putri Yangga Puspita, Berliana; Ari Nugrahanta, Gregorius (Jurnal Muara Pendidikan, 2024)
Broad-minded character is understood as a person’s perspective to view themselves comprehensively, to be responsive, to make decisions, and to behave positively. The low reading interest among children and the prevalence of bullying cases illustrated a lack of broad-minded character. This study aimed to develop a textbook on road civilization based on Project-Based Learning (PjBL) to foster broad-minded character. This research used the Research & Development (R&D) method with the ADDIE model. Ten certified teachers were involved in the needs analysis, five teachers and five experts acted as expert judges and eight children participated as limited trial subjects. The study results showed that (1) the textbook on road civilization based on Project-Based Learning to foster broad-minded character was developed following the ADDIE steps; (2) the quality of the book fell under the "Very Good" category (3.83 on a scale of 1–4) and did not require revisions; (3) the implementation of the textbook on home civilization based on Project-Based Learning significantly influenced broad-minded character (p < 0.05) with a large effect size (r = 0.99), equivalent to 98%. The effectiveness level was categorized as "High" (N-gain score of 84.66%). Based on the research findings, the development of the textbook on road civilization based on PjBL significantly fostered children’s broad-minded character.